2022
DOI: 10.1186/s12884-022-04463-y
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of women with hypertensive disorders of pregnancy: a scoping review

Abstract: Background Hypertensive disorders of pregnancy (HDP) constitute one of the leading causes of maternal and perinatal mortality worldwide, and are associated with an increased risk of recurrence and future cardiovascular disease. HDP affect women’s health condition, mode of birth and timing, length of hospital stay, and relationship with their newborn and family, with future life repercussions. Aims To explore the experiences of women with HDP from p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…Findings of qualitative perinatal studies identified similar emotions experienced by women after an unexpected diagnosis of high-risk pregnancy, 43,44 hypertensive disorder, 45,46 preterm labor, 47 and early pregnancy loss. 48 The concept of unmet expectations and broken or shattered expectations identified in this review was also described in studies of unexpected stillbirth, 49 perinatal loss, 50 preterm birth, 51 fetal anomaly, 7,8 and newborn admission to the neonatal intensive care unit.…”
Section: Discussionmentioning
confidence: 88%
“…Findings of qualitative perinatal studies identified similar emotions experienced by women after an unexpected diagnosis of high-risk pregnancy, 43,44 hypertensive disorder, 45,46 preterm labor, 47 and early pregnancy loss. 48 The concept of unmet expectations and broken or shattered expectations identified in this review was also described in studies of unexpected stillbirth, 49 perinatal loss, 50 preterm birth, 51 fetal anomaly, 7,8 and newborn admission to the neonatal intensive care unit.…”
Section: Discussionmentioning
confidence: 88%
“…One of the main causes of maternal and perinatal death worldwide is hypertensive disorders of pregnancy (HDP), which are also linked to a higher risk of recurrence and future cardiovascular disease. Women's health conditions, methods of delivery, hospital stays, and relationships with their children and families are all impacted by HDP [1]. One of the types and clinical symptoms of hypertension diseases during pregnancy is eclampsia [2].…”
Section: Introductionmentioning
confidence: 99%
“…One of the types and clinical symptoms of hypertension diseases during pregnancy is eclampsia [2]. In Nigeria, it is still one of the main factors contributing to maternal and neonatal morbidity and mortality [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…A scoping review of women's experiences of hypertensive disorders (Sakurai et al, 2022) revealed that it brought a crisis to their own health and their babies, how they coped and struggled, developed a fear of the future, and their positive and negative exchanges with HCPs. When diagnosed with HDP then hospitalized, women have another opportunity to understand their condition and develop knowledge of the disease.…”
Section: Introductionmentioning
confidence: 99%